2016
DOI: 10.1039/c6ra22586a
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of multi-responsive functional graphene quantum dots for sensing metal cations

Abstract: Aminated and phosphorylated graphene quantum dots (PiNGQDs) have been synthesized and used as fluorescent probes for sensing metal cations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In addition, the fabrication of amine‐functionalized N‐GQDs studied by Chen and co‐workers 146 had introduced carbon source of tris(hydroxymethyl) aminomethane together with CA and resulted in PLQY of 59.2%. From research studies, the utilization of CA as resources showed good performance in the GQDs development through the hydrothermal method 147,148 …”
Section: Synthesis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the fabrication of amine‐functionalized N‐GQDs studied by Chen and co‐workers 146 had introduced carbon source of tris(hydroxymethyl) aminomethane together with CA and resulted in PLQY of 59.2%. From research studies, the utilization of CA as resources showed good performance in the GQDs development through the hydrothermal method 147,148 …”
Section: Synthesis Methodsmentioning
confidence: 99%
“…From research studies, the utilization of CA as resources showed good performance in the GQDs development through the hydrothermal method. 147,148 Wang et al 149 synthesized GQDs using pyrene, as shown in Figure 11A and had a high yield of 63% PLQY with the emission of bright green fluorescence. The TEM images of GQDs in Figure 11B shows excellent uniformity of lateral size in the dispersion while the defect-free GQDs is seen in Figure 11C with 0.21 nm spacing size refers to graphene (100) plane.…”
Section: Hydrothermal Methodsmentioning
confidence: 99%